Superhydrophobic Surface from Sol Gel Synthesis of Thin Sol Gel Fluorinated Silica Coating - Othman, Norfazlinayati; Harun, Mohd Hamzah; Zaharuddin, Izzuddin Mohamad; Ezani, Nor Adnin Ezani Mohd; Mohamed, Mahathir; Alias, Mohd Sofian (Balai Publikasi Indonesia, 2026)
A thin fluorinated silica coating was synthesized via a sol–gel route using silica nanoparticles as surface roughness agents functionalized with long-chain fluoroalkylsilane. The coatings were characterized for surface wettability, optical transmittance, infrared spectra, and morphology. All samples exhibited excellent optical transparency as verified by UV–visible spectroscopy. The fluorinated silica coating demonstrated markedly enhanced water repellency compared to TEOS and TEOS–FAS systems, confirming the critical role of fluorinated silica in improving hydrophobicity. These findings indicate its strong potential for application as a transparent hydrophobic coating in optoelectronic devices, lenses, and window materials